OP0283 Ultrasonographic evaluation in rheumatoid arthritis using the global omeract/eular ultrasound synovitis score (GLOESS). (15th June 2017) - Stoenoiu, MS; Pesonen, A; Bello, N; Christensen, R; Østergaard, M; Naredo, E; Terslev, L
Abstract : Background: Recently, a gl obal O MERACT/E ULAR ultrasound (US) s ynovitis s core (GLOESS) combining grey-scale (GS) and power-Doppler (PD) scores has been proposed as a novel measurement tool to assess disease activity and response to therapy in patients with rheumatoid arthritis (RA) 1, 2 . However, the ability of GLOESS to differentiate patients with different states of disease activity vs. remission in standard clinical care is not known. Objectives: To assess the ability of GLOESS to discriminate between different clinical states of activity vs. remission in RA patients, and to compare clinical, GLOESS and PD US remission criteria and scores in a cross-sectional study. Methods: Eighty RA patients from 3 centres were recruited at consecutive clinical visits: 50% were in remission and 50% had active RA according to Simple Disease Activity Index (SDAI). SDAI, Clinical Disease Activity Index (CDAI), 28-joint Disease Activity Score (DAS 28CRP), Health Assessment Questionnaire (HAQ), ACR/EULAR remission criteria were assessed. An independent investigator unaware of clinical results performed all US joint examinations of 26 joints. GLOESS, PD, and GS US sum scores per patient were assessed using OMERACT definitions. PD US remission was defined as the PD sum score =0. GLOESS remission was defined as GLOESS score ≤1 thereby also including possible GS grade 1. Results: PD US remission was observed in 38 (48%) patients and GLOESS remission in 16 (20%) patients. SDAI (r=0.24; p=0.03) and CDAI (r=0.23; p=0.04) but not DAS28CRP (r=0.21; p>0.05) were weakly correlated with GLOESS scores in the whole joint set. SDAI (r=0.41; p<0.001), CDAI (r=0.40; p<0.001), and DAS28CRP (r=0.40; p<0.001) were moderately correlated with PD activity in the whole joint set. A minority of patients were classified both in GLOESS remission and in clinical remission according to SDAI (n=10), to CDAI (n=10), to DAS28CRP (n=10) and to ACR/EULAR 2011 (n=7). Less than one third of patients were classified both in PD US remission and in clinical remission according to SDAI (n=22), to CDAI (n=26), to DAS28CRP (n=27) and to ACR/EULAR 2011 (n=21). The proportion of patients in clinical remission was significantly different according to the definition considered: while 50% of the patients (n=40) were classified in remission according to SDAI, 58% (n=46) were classified in remission according to DAS28CRP, and 43% (n=34) according to CDAI and 43% (n=34) according to ACR/EULAR 2011 remission criteria. Conclusions: We document major discrepancies between US and clinical findings and between clinical scores classifying patients in active disease vs. remission. Patients reaching GLOESS or PD US definitions of remission are partly different from those reaching clinical definitions of remission. References: Naredo E, et al. The OMERACT ultrasound task force–status and perspectives. J Rheumatol. 2011;38(9):2063–2067. D'Agostino MA, et al. Exploring a new ultrasound score as a clinical predictive tool in patients with rheumatoid arthritis starting abatacept: results from the APPRAISE study. RMD Open. 2016 5;2(1):e000237. doi: 10.1136/rmdopen-2015–000237. Acknowledgements: We acknowledge P. Durez, B. Lauwerys, A. Durnez, A. Nzeusseu Toukap, F.A. Houssiau for fruitful discussions and/or contribution to recruitment. Disclosure of Interest: None declared